The Existence of Christian Community Hamlet Tulungrejo, Glenmore District Banyuwangi Regency in 1911-2016 - Agnes Intan P.W; Kayan Swastika; Sugiyanto Sugiyanto (History Education, University of Jember, 2018)
Existence of the Community of Krsiten located in Tulungrejo, Glenmore Banyuwangi regency began in 1911 until the Year 2016. The formation of this Christian Community started from the Migration conducted by the Javanese in Jombang and Makung Tulungrejo Area as a regional Center for the spread of Christianity. The problems in this research are; how the background and the beginning of the formation of the Tulungrejo Community Christian Community in 1911 ?; and how is the life of Tulungrejo Community Christian Community 1912-2016 ?. The purpose of this research is To analyze the background and early formation of the Tulungrejo Community Christian Community in 1911, and To analyze the life of the Christian Community Tulungrejo Hamlet in 1912-2016. The research method used is historical research method. The conclusion of this study is the beginning of the emergence of this community started since the migration made by some Javanese Javanese who moved to the Tulungrejo area and make the area as the base of spreading the Christian religion east of East Java. Keywords: The Christian community, Tulungrejo